Development of Mathematics Learning Video Media Based on Realistic Mathematics Education (RME) in Grade V at MIN 1 Serang - Iis, Iis Rohmayanti; Sari Dewi, Ratna; Adya Pribadi, Reksa (LPPM Universitas Primagraha, 2024)
This research aims to develop a Mathematics learning video media based on Realistic Mathematics Education (RME) with the involvement of teachers in the development process and testing the effectiveness of the media product through the expert testing stage and to find out how students respond to the Realistic Mathematics Education (RME) based Mathematics learning video media. ) were developed. This research uses the Research & Development (R&D) research method using the ADDIE model, with several stages, namely Analysis, Design, Development, Implementation, Evaluation. This research was conducted at MIN 1 Serang with 27 VA class students as research subjects with details of students in limited trials. The instrument used is a questionnaire sheet for validation of material experts, media experts and language experts as well as student responses. The research results obtained were the feasibility of Realistic Mathematics Education (RME)-based Mathematics learning video media based on expert assessment, obtaining the criteria